Penggunaan Inventory Turn Over dalam menentukan Purchase Order sebagai Syarat Pemesanan Barang Distributor - Mardiana Mardiana; Fergian Octa Yuliawan; Muhammad Rizki Abror (UNIVERSITAS RAHARJA, 2022)
PT. Multisari Langgengjaya is a company engaged in the distributor for food and beverages, as well as the sole distributor or distributor of the food company PT. Marizarasa Sarimurni. Distributor companies currently need information about the trading products that are governed by the management of logistics. Especially the management of distributor warehouse with a lot of product item quantity, so the needed product procurement plan in the Logistics section. It is currently at PT. Multisari Langgengjaya is quite convincing by utilizing the standard of Inventory Turn Over (ITO) calculation that becomes the reference during the order process or Purchase Order (PO) with the manufacturer. Logistics became the first analyst as the determination of ordering goods to be stored by the warehouse for a period of one month ahead. In the research done will be seen how the ITO calculation determines the ordering of goods and how much it affects the logistics of PT. Multisari Langgengjaya. To analyse this research using Unified Modelling Language (UML) to illustrate the current procedures and processes